2017
DOI: 10.1002/ange.201703159
|View full text |Cite
|
Sign up to set email alerts
|

Initiator‐Loaded Gold Nanocages as a Light‐Induced Free‐Radical Generator for Cancer Therapy

Abstract: Tumor hypoxia greatly suppresses the therapeutic efficacy of photodynamic therapy( PDT), mainly because the generation of toxic reactive oxygen species (ROS) in PDT is highly oxygen-dependent. In contrast to ROS, the generation of oxygen-irrelevant free radicals is oxygen-independent. An ew therapeutic strategy based on the light-induced generation of free radicals for cancer therapyi sr eported. Initiator-loaded gold nanocages (AuNCs) as the free-radical generator were synthesized.U nder near-infrared light (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Polymer cleavage-mediated exposure of buried ligand, 47 removal of photolabile group, 48 and photocaging group 9 Cell adhesion, 47 release and patterning, 48 and in vivo cell adhesion 9 NIR-based upconversion materials UV-cleavage of ligand, 49 molecular cage, 10 and photoisomerization 50 by NIR-based upconversion using UCNPs Cell adhesion and release, 49,50 drug delivery, 10,58 in vivo stem cell differentiation, 10 and cell polarization 58 Photothermal materials NIR-based heat generation with gold nanorods, 51 silver triangles, 53 magnetite, 54 and NIR-based nanobubble formation 55 Photothermal hyperthermia, 51,53,54 photodynamic therapy, 59,60 and cell adhesion and release 56 In situ self-assembly…”
Section: Uv-based Photolabile Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer cleavage-mediated exposure of buried ligand, 47 removal of photolabile group, 48 and photocaging group 9 Cell adhesion, 47 release and patterning, 48 and in vivo cell adhesion 9 NIR-based upconversion materials UV-cleavage of ligand, 49 molecular cage, 10 and photoisomerization 50 by NIR-based upconversion using UCNPs Cell adhesion and release, 49,50 drug delivery, 10,58 in vivo stem cell differentiation, 10 and cell polarization 58 Photothermal materials NIR-based heat generation with gold nanorods, 51 silver triangles, 53 magnetite, 54 and NIR-based nanobubble formation 55 Photothermal hyperthermia, 51,53,54 photodynamic therapy, 59,60 and cell adhesion and release 56 In situ self-assembly…”
Section: Uv-based Photolabile Materialsmentioning
confidence: 99%
“…The generated alkyl radicals impair DNA to induce the apoptosis of cancer cells. 59 In another study, Fe ion that can catalyze the generation of reactive oxygen species was used for photodynamic therapy. Upon NIR irradiation, an antiferromagnetic pyrite leads to in situ surface oxidation and maintains H 2 O 2 disproportionately to catalyze ·OH generation to enable photodynamic therapy, which is further facilitated by heat-induced Fenton process.…”
Section: Nir-controlled Photothermal and Photodynamic Therapymentioning
confidence: 99%
“…Furthermore, the NIR-region absorbance endowed by the hollow nanocage structures corresponds to the photothermal therapeutic wavelength window, which does not overlap with the light absorbing region of substances in the body such as hemoglobin, fat, and water. Since the tissue penetration of NIR light is superior to that of visible light and ultraviolet rays, it presents huge advantages when combined with hollow nanoparticles [134][135][136][137][138][139][140][141][142][143].…”
Section: Conventional Shape Control By Galvanic Replacementmentioning
confidence: 99%
“…This kind of oxygen-independent alkyl free radicals could be generated in large amounts even in the hypoxic tumor, which show a great potential for overcoming the limitation of the oxygen-dependent therapy especially in hypoxic tumor therapy. Because of the enhanced permeability of tumor vasculature and poor lymphatic drainage in the tumor microenvironment, nanoparticles, such as the Au nanocages [13 , 14] , GuS [15] , Nb 2 C [16] were extensively utilized as carriers to deliver the alkyl free radicals for improved hypoxic tumor therapy. However, it is reported that only 0.7% of the administered nanoparticle could be delivered to a targeted solid tumor during long blood circulation [17] .…”
Section: Introductionmentioning
confidence: 99%